Chiinese Training Courses for African Officials: a "Win-Win" Engagement? - Henry Tugendhat (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2014)
As part of its growing engagement in Africa, China has become one of the world's largest providers of short-term agricultural training courses. China's training course model differs from most other traditional donors in that it almost exclusively targets government officials. These courses aim to facilitate the transfer of knowledge and technology, increase trade opportunities, foster stronger political and economic relationships, and present a positive image of China. This research concludes that the courses appear to be achieving these goals, with different benefits for both sides.
Keywords: 330